Population structure and genetic diversity of Mi pigs based on SINE-RIPs - Wang, Xiaoyan; Zhou, Chenyu; Zheng, Yao; Yu, Miao; He, Jia; Chen, Cai; Qiao, Suwei; Moawad, Ali Shoaib; Tian, Guoxing; Li, Bixia; Song, Chengyi (Frontiers in Veterinary Science, 2025)
Mi pigs, a Chinese native breed found in Jintan and Yangzhong in Jiangsu Province, were recorded as having only a few hundred members in the latest national livestock and poultry genetic resources survey. To explore their conservation and breeding prospects, 18 SINE Retrotransposon Insertion Polymorphisms (sine-rips) were analyzed using PCR to assess the population structure and genetic diversity of Mi pigs. These pigs were grouped into eight families based on a UPGMA phylogenetic tree. The genetic distances between the Mi pig populations and commercial breeds ranged from 0.3712 to 0.7609, indicating significant divergence. Conversely, they showed a closer genetic relationship with other local Jiangsu breeds, with distances varying from 0.0943 to 0.6122, a finding supported by the UPGMA tree. The populations displayed a substantial degree of outbreeding, with Fis values from −0.4744 (M5) to −0.0847 (M8) and Fst values from 0.0534 (M3, M8) to 0.2265 (M2, M7), highlighting their genetic diversity which is crucial for the conservation of Mi pigs. Despite this diversity, the population sizes were uneven, with M5, M7, and M8 having 6, 5, and 7 individuals, respectively. These findings lay a theoretical foundation for the ongoing conservation and breeding efforts for Mi pigs.